Left Ventricular Function in Steroid-Resistant Nephrotic Syndrome At Dr. Hasan Sadikin Hospital - Kusumaputri, Aghnia Ghassani; Rahayuningsih, Sri Endah; Rossanti, Rini; Apandi, Putria Rayani; Widiasta, Ahmedz (Faculty of Medicine, Universitas Padjadjaran, 2025)
Steroid-resistant nephrotic syndrome (SRNS) is a nephrotic syndrome (NS) which does not respond to high-dose corticosteroid therapy after 4 to 8 weeks. SRNS occurs in approximately 10–20% of childhood idiopathic nephrotic syndrome. SRNS patients are at risk of developing cardiovascular complications due to the long duration of the disease. This retrospective descriptive study investigated left ventricular function in pediatric patients with steroid-resistant nephrotic syndrome (SRNS) at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from 2018 to 2022. A total of 42 patients aged 1 month to 18 years who underwent transthoracic echocardiography (TTE) were included. Left ventricular function was assessed using ejection fraction (EF) and fractional shortening (FS). Most patients (61.9%) had normal EF and FS values, while 38.1% showed decreased systolic function. The mean EF and FS were 55.8% and 30.2%, respectively, with median values of 59.3% and 31.2%. An important finding in this study is that some children with SRNS exhibited decreased EF and FS values despite having no other identifiable risk factors for ventricular dysfunction, such as congenital heart disease (CHD), rheumatic heart disease (RHD), chronic kidney disease (CKD), or hypertension. This finding sugest that ventricular dysfunction may still occur independently in some cases of SRNS.